Inhibition of hepatitis B virus DNA replication by imino sugars without the inhibition of the DNA polymerase: therapeutic implications. - Mehta, A; Carrouée, S; Conyers, B; Jordan, R; Butters, T; Dwek, R; Block, T (2001)
Previously we have shown that the imino sugar inhibitor of N-linked glycan processing, N-nonyl-deoxynojirimycin (N-nonyl-DNJ), had antiviral activity in the woodchuck model of chronic hepatitis B virus (HBV) infection. In studying the mechanism of action of this compound, it was discovered that imino sugars could inhibit HBV secretion without inhibiting N-linked glycoprocessing. Although N-nonyl-DNJ is an inhibitor of the endoplasmic reticulum (ER) glucosidase, here it is shown that N-nonyl-DNJ retained antiviral activity at concentrations that had no significant impact on ER glucosidase function. Taken together, these results suggested that N-nonyl-DNJ possessed an antiviral activity attributable to a function other than an impact on glycoprocessing. This hypothesis was confirmed by experiments showing that N-nonyl-deoxygalactojirimycin (N-nonyl-DGJ), an alkyl derivative of galactose with no impact on glycoprocessing, retains anti-HBV activity. The data suggest that N-nonyl-DGJ exerts its antiviral action at a point before viral envelopment and may prevent the proper encapsidation of the HBV pregenomic RNA.